SAT0461 Characterisation of different low disease activity measurements in patients with psoriatic arthritis. (15th June 2017) - Coates, LC; Gottlieb, AB; Merola, JF; Aikman, L; Szumski, A; Chhabra, A
Abstract : Background: Selection of the correct target to guide treatment is crucial for effective disease management in patients with psoriatic arthritis (PsA). Objectives: To evaluate the prognostic value of several low disease activity (LDA) measurements in patients with PsA and psoriasis to assist physicians choose a valid target that facilitates assessment in clinical practice. Methods: This was a post-hoc analysis from the PRESTA 1 clinical study. LDA targets analyzed were: Disease Activity in PsA (DAPSA) LDA ≤14 (tender joint count [TJC], swollen joint count [SJC], patient global visual analog scale [Pt VAS], pain VAS, C-reactive protein [CRP]; clinical (c)DAPSA LDA ≤13 (DAPSA without CRP); and minimal disease activity (MDA) measurement defined as 5/7 cut-offs (TJC ≤1, SJC ≤1, psoriasis activity and severity index [PASI] ≤1, Pt pain ≤15mm, Pt VAS ≤20mm, health assessment questionnaire ≤0.5, tender entheseal points ≤1). Additional MDA measurements were investigated where 5/7 cut-offs were met but some were mandated: MDA_joint with both TJC and SJC cut-offs mandated, MDA_skin where PASI cut-off was mandated, MDA_joint+skin where the TJC, SJC, and skin cut-offs were mandated. Results: At Week 24, the proportion of patients achieving LDA were 47%, 20%, 38%, 14% in MDA 5/7, MDA_skin, MDA_joint, MDA_joint+skin, respectively, vs ∼71% in DAPSA and cDAPSA LDA. The highest proportion of discordance was observed between MDA_skin or MDA_joint+skin with DAPSA LDA or cDAPSA LDA (Figure). The majority of patients had no residual arthritis although levels were highest in the DAPSA measurements (Table). However, notable residual levels of psoriasis were observed in measurements that did not require skin disease control (Table 1 ). MDA_joint+skin had the lowest levels of residual disease across all cut-offs (Table 1 ). At Week 12, a significant difference (P<0.05) between the 50mg etanercept (ETN) once a week and 50mg ETN twice a week cohorts was observed in the measurements that required a skin cut-off (MDA_skin and MDA_joint+skin) and MDA 5/7 but not in DAPSA LDA, cDAPSA LDA, or MDA_joint. Conclusions: DAPSA and cDAPSA LDA provided the least stringent cut-offs with the highest percentages of patients with residual disease. Whilst choosing the optimal target for treatment requires more debate, it is clear from these data that levels of residual psoriasis are high in those measurements that do not require skin control. If this is not included in a treatment target for PsA, notable levels of psoriasis can be missed. References: Sterry W, et al. BMJ 2010;340:c1471. Disclosure of Interest: L. Coates Grant/research support from: Abbvie, Janssen, Consultant for: Abbvie, BMS, Janssen, Lilly, MSD, Novartis, Pfizer, A. Gottlieb Grant/research support from: Centocor (Janssen), Amgen, Abbvie, Novartis, Celgene, Pfizer, Lilly, Levia, Merck, Xenoport, Dermira, Baxalta, Consultant for: Amgen, Astellas, Akros, Centocor (Janssen), Celgene, Bristol Myers Squibb, Beiersdorf, Abbvie, TEVA, Actelion, UCB, Novo Nordisk, Novartis, Dermipsor, Incyte, Pfizer, Canfite, Lilly, Coronado, Vertex, Karyopharm, CSL Behring Biotherapies for Life, Glaxo Smith Kline, Xenoport, Catabasis, Meiji Seika Pharma, Takeda, Mitsubishi, Tanabe Pharma Development America, Genentech, Baxalta, Kineta One, KPI Therapeutics, Crescendo Bioscience, Aclaris, Amicus, Reddy Labs, Speakers bureau: Abbvie, J. Merola Consultant for: Biogen IDEC, AbbVie, Amgen, Eli Lilly, Novartis, Pfizer, Janssen, UCB, Kiniksa, Momenta and Mallinckrodt, L. Aikman Shareholder of: Pfizer, Employee of: Pfizer, A. Szumski Employee of: InVentiv Health, A. Chhabra Shareholder of: Pfizer, Employee of: Pfizer